A Comparative Study of Plate Structure Analysis using Strip Method, PBI 71, and FEM - Adityawarman, Guntara M. (Teknik dan Ilmu Komputer, 2015)
AbstrakÃÂ Struktur yang memikul momen pada umumnya adalah pelat lantai, balok, dan kolom. Pelat lantai merupakan elemen struktur yang secara langsung mendapatkan beban hidup selain beban tambahan dan berat sendiri. Metode analisis lendutan menggunakan strip method dan FEM (SAP2000) sedangkan analisis momen tumpuan dan lapangan menggunakan strip method, koefisien momen (PBI 71), dan FEM (SAP2000). Studi kasus ini bertujuan untuk mengetahui perbedaaan lendutan dan momen dari ketiga metode tersebut. Hasil Studi kasus pada pelat beton ukuran ly = 4 m dan lx = 3 m, memberikan nilai lendutan dengan menggunakan strip method dan FEM (SAP2000), yaitu 0,255 mm dan 0,412 mm. Analisis momen tumpuan dan lapangan dengan menggunakan strip method lebih besar dari metode koefisien momen PBI 71 dan FEM (SAP2000).ÃÂ Kata kunci: strip method, pelat, SAP2000, koefisien momenÃÂ ÃÂ AbstractÃÂ Structures bearing moments are in general slab, beams and columns. Slab is a structural element that directly bear the live load in addition to the extra load and its own weight . Deflection analysis method employs the strip method and FEM (SAP2000) while the negative and positive moment analysisÃÂ uses the strip method, moment coefficient (PBI 71), and FEM (SAP2000). This case study aims to determine the differences in deflection and moments of the three methods. The results of the case study on the concrete slab of ly = 4 m and lx = 3 m, show the deflection values by using the strip method and FEM (SAP2000) that are ÃÂ 0.255 mm and 0.412 mm. The negative and positive moment analysis by using the strip method is larger than moment coefficient method (PBI 71) and FEM (SAP2000)ÃÂ Key words: strip method, plate, SAP2000, moment coefficient